Low-temperature adaptation of Chaetomium madrasense, a symbiotic gut fungus of amphipods in the Mariana Trench: cellulase activity and transcriptome analysis - Ji, Paiyao; Cui, Yukun; Xiao, Yu; Wan, Shicong; Fang, Jiasong; Yu, Xi (Frontiers in Marine Science, 2025)
Hadal amphipods have developed unique survival strategies to cope with extreme conditions, such as low temperatures and high hydrostatic pressure, with their gut microbes playing a crucial role in this adaptation. Nevertheless, the specific mechanisms and functional contributions of these microbial communities remain poorly understood. In this study, a gut symbiotic fungus, Chaetomium madrasense HM411, which has cellulose degrading ability, was isolated in the gut of Hirondellea gigas from the Mariana Trench. Comparison of enzyme production between the terrestrial and deep-sea strains of C. madrasense (HM412 and HM411, respectively) showed that the deep-sea strain exhibited significantly higher endoglucanase activity at 15°C, representing a 1.2-fold increase. Furthermore, growth rate analysis indicated that C. madrasense HM411 maintained significantly higher proliferation rates at 15°C, suggesting psychrotolerant traits in the deep-sea derived strain. Transcriptomic analysis revealed distinct low-temperature enzyme production advantages in C. madrasense HM411 compared to strain HM412, particularly in the regulation of Carbohydrate-Active Enzymes, extracellular enzyme secretion, stress protein production, and cell wall/membrane modifications. These findings suggest that C. madrasense HM411 may have evolved unique enzymatic and genomic adaptations to thrive in hadal environments, potentially playing important roles in recalcitrant substance degradation under extreme conditions.